Untangling Effects of Human Disturbance and Natural Factors on Mortality Risk of Migratory Caribou - Plante, Sabrina; Dussault, Christian; Richard, Julien H.; Garel, Mathieu; Côté, Steeve D. (Frontiers in Ecology and Evolution, 2020)
Human disturbances are rapidly increasing in northern and Arctic regions, raising concerns about the recovery and persistence of declining caribou (Rangifer tarandus) populations. Yet, the consequences of behavioral responses towards human disturbances on vital rates have rarely been investigated. Here, we assessed the cumulative and instantaneous effects of human disturbances (road, human settlements, mines and mining exploration) at different temporal scales on the mortality risk of 254-GPS collared migratory caribou monitored in two herds, the Rivière-aux-Feuilles (RFH) and Rivière-George (RGH) herds, in northern Québec and Labrador, Canada. We also assessed the relative importance of human disturbances on caribou mortality risk compared to non-anthropogenic factors, including habitat use by caribou, predation risk by wolves, and local weather conditions. Human disturbances alone had a limited impact on caribou mortality risk. Repeated exposure to disturbances did not increase mortality risk during the early-life period (1-7 years), but more abundant precipitations (RFH) or the use of areas with a higher predation risk (RGH) did. At the seasonal scale, non-anthropogenic factors, particularly patterns of habitat use by caribou and air temperature, prevailed over anthropogenic factors to define mortality risk in the RFH. Caribou of the RFH using habitat selectively targeted at the population level more frequently decreased their chance of mortality during winter, whereas individuals using warmer areas during summer faced a higher risk of mortality. At the daily scale, we found that anthropogenic and non-anthropogenic factors generally had either no effect on the daily risk of mortality, or their effects were undistinguishable from the effect of latitude with which they were highly correlated. The only exception was for the RFH in winter, for which the daily risk of mortality increased by 10 times for each 10-km increment towards industrial disturbances. Although the impacts of human disturbances on caribou survival were limited, we nevertheless detected a negative effect on survival on the RFH, even at the currently low level of human development. Our study highlights the importance of assessing the effect of human disturbances at various spatiotemporal scales, and of considering the relative influence of other non-anthropogenic factors to fully understand what drives wildlife populations.